Supporting Self-management Among Young People With Acne Vulgaris Through a Web-Based Behavioral Intervention: Development and Feasibility Randomized Controlled Trial - Athena Ip; Ingrid Muller; Adam W A Geraghty; Kate Rumsby; Beth Stuart; Paul Little; Miriam Santer (JMIR Publications, 2021)
BackgroundAcne is a common skin condition that is most prevalent in young people. It can have a substantial impact on the quality of life, which can be minimized with the appropriate use of topical treatments. Nonadherence to topical treatments for acne is common and often leads to treatment failure. ObjectiveThe aim of this study is to develop a web-based behavioral intervention to support the self-management of acne and to assess the feasibility of recruitment, retention, and engagement of users with the intervention. MethodsThe intervention was developed iteratively using the LifeGuide software and following the person-based approach for intervention development. The target behavior was appropriate use of topical treatments. Barriers and facilitators identified from the qualitative research and evidence from the wider literature were used to identify techniques to improve and promote their use. Young people with acne aged 14-25 years who had received treatment for acne in the past 6 months were invited to participate through mail-out from primary care practices in the South of England in a parallel, unblinded randomized trial. Participants were automatically randomized using a computer-generated algorithm to usual care or to usual care plus access to the web-based intervention. Usage data was collected, and a series of questionnaires, including the primary outcome measure for skin-specific quality of life (Skindex-16), were collected at baseline and at the 4- and 6-week follow-ups. ResultsA total of 1193 participants were invited, and 53 young people with acne were randomized to usual care (27/53, 51%) or usual care plus intervention (26/53, 49%). The response rate for the primary outcome measure (Skindex-16) was 87% at 4 weeks, 6 weeks, and at both time points. The estimate of mean scores between groups (with 95% CI) using linear regression showed a trend in the direction of benefit for the web-based intervention group in the primary outcome measure (Skindex-16) and secondary measures (Patient Health Questionnaire-4 and the Problematic Experiences of Therapy Scale). Intervention usage data showed high uptake of the core module in the usual care plus web-based intervention group, with 88% (23/26) of participants completing the module. Uptake of the optional modules was low, with less than half visiting each (myth-busting quiz: 27%; living with spots or acne: 42%; oral antibiotics: 19%; what are spots or acne: 27%; other treatments: 27%; talking to your general practitioner: 12%). ConclusionsThis study demonstrated the feasibility of delivering a trial of a web-based intervention to support self-management in young people with acne. Additional work is needed before a full definitive trial, including enhancing engagement with the intervention, recruitment, and follow-up rates. Trial RegistrationISRCTN 78626638; https://tinyurl.com/n4wackrw